Comparing the practices of US hockey against a global model for integrated development of mass and high-performance sport. Issue 3 (3rd March 2020) - Smolianov, Peter; Marc-Aurele, Connor; Norberg, Jaclyn; Dion, Steven; Schoen, Christopher; Jensen, Jake
ABSTRACT: This study examines the current state of hockey in the USA against an ideal-type model for developing high performance sport integrated with mass participation. A questionnaire was developed for the following elements of the model: talent development; advanced athlete support; training centers; competitions; intellectual services; partnerships with supporting agencies; and balanced and integrated funding and structures of mass and elite sport. Twelve international experts, including executives from sport governing bodies, swim coaches, academicians, and administrators, validated the survey questions. To determine the areas for improvement, 111 coaches completed the questionnaire. Possible advancements were further identified through semi-structured discussions with 15 hockey administrators. Results suggest possible enhancements at macro-level (e.g., new partnerships and incentives for greater support of mass and elite hockey), meso-level (e.g., additional sources and models for better coach education and facilities), and micro-level (e.g., advanced lifelong hockey guidelines for excellence of everyone).